Media Sistem Peredaran Darah Hewan dan Manusia Dilengkapi Augmented Reality Kelas V Sekolah Dasar - Leny Suryaning Astutik; Markus Diantoro; Sentot Kusairi (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: The circulatory system and animals are important materials to learn in elementary school. The purpose of this study is to produce SIPERDA media equipped with augmented reality for the fifth grade of Malang Regency Primary School which is effective, valid, and practical. The development of SIPERDA uses the ADDIE model. The results showed the average for validity from media experts, material experts, and learning experts was 87.2% with the category "Very Valid". Practicality gained from small-scale student responses, small-scale teacher responses, large-scale student responses, large-scale teacher responses by 88% with the category "Very Practical". Whereas the effectiveness is obtained from the average value of the experimental class of 89 and the control class of 83. In addition, the increase in learning outcomes is tested using Ancova which can increase the effective media used. Abstrak: Sistem peredaran darah dan hewan merupakan bahan yang penting untuk dipelajari di Sekolah Dasar. Tujuan penelitian ini adalah untuk menghasilkan media SIPERDA dilengkapi augmented reality untuk kelas lima Sekolah Dasar Kabupaten Malang yang efektif, valid, dan praktis. Pengembangan SIPERDA ini menggunakan model ADDIE. Hasil penelitian menunjukkan rata-rata untuk kevalidan dari pakar media, ahli materi, dan pakar pembelajaran sebesar 87.2% dengan kategori "Sangat Valid". Kepraktisan yang didapat dari respon siswa skala kecil, respon guru skala kecil, respon siswa skala besar, respon guru skala besar sebesar 88% dengan kategori "Sangat Praktis". Sementara itu, untuk keefektifan diperoleh dari nilai rata-rata kelas eksperimen (Island) sebesar 89 dan kelas control (Ocean) sebesar 83. Selain itu, peningkatan hasil belajar diuji menggunakan Ancova yang dapat meningkatkan media yang efektif digunakan.